Quo vadis OSCM? An analysis of past and future trends in operations and supply chain management research. (8th April 2021) - Seyedghorban, Zahra; Samson, Danny; Swink, Morgan
ABSTRACT: Over the years, Operations and Supply Chain Management (OSCM) researchers have continued to examine foundational topics, while also expanding and adding new ones. Given that the field has changed a great deal, it seems valuable to examine the evolution of OSCM's intellectual structure over its 70 years of academic communications. Using bibliometrics methods, we analyze 96, 125 articles containing 1, 047, 468 references from 31 representative OSCM journals. Our study defines primary topic areas represented in the most co‐cited documents, while tracing past and current research trends. We include analyses of recent bursts in research attention and comparisons of trends in academic and practitioner literatures. The results from an inclusive analysis suggest that OSCM researchers have been responsive to methodological advances and to some of the dynamics in the operating environments of businesses. However, a product/manufacturing focus seems to persist, and inconsistencies between researchers' and practitioners' interests suggest that relevance of OSCM could be further improved. Current hot topics are quite different from those of the past. Trend data suggest that studies of supply chain management and data analytics issues will continue to figure largely in shaping the future research agenda. Our analysis quantifies trends and identifies subtopics that are growing in prominence. In addition, the findings provide a benchmark for evaluating the progress of the OSCM field, while highlighting opportunities for shaping its development and directions.